Southern South China Sea boundary current transition from summer to winter - Tian, Yilun; Zuo, Juncheng; Shu, Yeqiang; Wang, Qiang; Xie, Yi; Ji, Qiyan; Liu, Xing; Wang, Zhizu; Wu, You; Zhang, Yuting (Frontiers in Marine Science, 2023)
The characteristics and mechanism of the southern South China Sea (SCS) Western Boundary Current (WBC) summer-winter transition have been investigated. The transition typically starts in early October and lasts for about two weeks. Above the thermoclines (~100 m), the transition is simultaneous with depth, while below the thermoclines the transition in deeper layer significant lags that in the shallow layers. The geostrophic balance dominates the transition of WBC. Above the thermocline, the transition is determined by the barotropic pressure gradient component. Below the thermocline, the transition is determined by the competition between the barotropic and baroclinic pressures components. When the southern SCS WBC transition above the thermocline starts, the barotropic and baroclinic pressures components offset each other below the thermocline, resulting in the lag of the geostrophic balance. With the depth increases, more time is needed for the barotropic pressures component to enhance enough to dominate a geostrophic balance, which induces the transition lag with depth. Changes in the barotropic pressure gradient component are mainly due to the variations in SCS basin scale wind stress curl, while changes in the baroclinic pressure gradient component below the thermocline are associated with the warming of the deeper water column caused by the downwelling near the continental slope and the disappearing of upwelling off Vietnam.